Eco-Sufism in the Light of the Qur’ān: A Thematic Study of Tafsir Al-Misbah by Muhammad Quraish Shihab - Nur Arfiyah Febriani; Ahmad Ridla Syahida; Thiyas Tono Taufiq (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
The concept of Eco-Sufism, as an environmental ethic, believes that nature is the tajalliyāt and image of asmā and the attributes of God, all of which have theological and humanist sensibilities. The Qur’ān confirms this view, stating that all nature surrenders (aslama), submits to God’s laws (qāniṭūn), purifies (sabbaḥa), prostrates (yasjudu) and prays (ṣalāt). This library research focuses on analysing Tafsir Al-Mishbah by Muhammad Quraish Shihab as a primary source. The content analysis approach is used to uncover the mufassir’s views on Eco-Sufism in his tafsir. In contrast, the mauḍūʿi (thematic) method is applied to explore the concept of Eco-Sufism in the Qur’ān. The results showed that the religiosity of the universe expressed through paradigmatic dialectics and Eco-Sufism terms can be understood as a form of the universe’s submission to the system established by Allah the Almighty. The universe’s harmony, aptitude and discernment are clues to the Power and Oneness of the Creator. However, various natural activities such as tasbīḥ, sujūd, and ṣalāt are variously interpreted as majāzi or ḥaqīqī. However, the servitude of nature expressed through the activity of the universe is proof that nature also has a soul and spiritual dimension, just like humans.Contribution: This paper theoretically provides a holistic view of Sufism in building an ideal relationship among humans, God and the environment, which is expected to produce pragmatic results for the rescue and protection of nature and the environment.